Identification of a new hemidesmosomal protein, HD1: a major, high molecular mass component of isolated hemidesmosomes (The Rockefeller University Press, 1992)
Hemidesmosomes (HDs) mediate cell adhesion to the extracellular matrix and have morphological association with intermediate-sized filaments (IFs) through cytoplasmic plaques. Though several proteins have been located in HDs, most of them have not been well characterized, with the exception of the 230-kD antigen of bullous pemphigoid (BP), an autoimmune skin blistering disease. Only recently we have succeeded in isolating HDs from bovine corneal epithelial cells and in identifying five major components on SDS-PAGE (Owaribe K., Y. Nishizawa, and W. W. Franke. 1991. Exp. Cell Res. 192:622-630). In this study we report on immunological characterization of one of the major components, termed HD1, with an apparent molecular mass of 500 kD. Immunofluorescence microscopy showed colocalization of HD1 with BP antigen at the basement membrane zone of those tissues that have typical HDs, including skin epidermis, corneal and tracheal epithelia, and myoepithelium. In cultured keratinocytes, HD1 demonstrated colocalization with BP antigen in the precise way, while being absent from focal adhesions. Immunoelectron microscopy revealed that an epitope of HD1 was located on the cytoplasmic side of HDs. Taking all these results together, we conclude that HD1 is a new hemidesmosomal component. Interestingly, HD1 also exists in endothelial and glial cells, which lack typical HDs.